On Stević-Sharma Operators from General Class of Analytic Function Spaces into Zygmund-Type Spaces. (1st July 2022) - Bakhit, M. A.; Kamal, A.
Abstract : A Stevic ′ -Sharma operator denoted by T ψ 1, ψ 2, φ is a generalization product of multiplication, differentiation, and composition operators. In this paper, we characterize the bounded and compact Stevic ′ -Sharma operator T ψ 1, ψ 2, φ from a general class X of Banach function spaces into Zygmund-type spaces with some of the most convenient test functions on the open unit disk. Using several restrictive terms, we show that all bounded operators T ψ 1, ψ 2, φ from X into the little Zygmund-type spaces are compact. As an application, we show that our results hold up for some other domain spaces of T ψ 1, ψ 2, φ, such as the Hardy space and the weighted Bergman space.